Love May Fail: A Novel - Quick, Matthew 1973- (New York, NY Harper, an imprint of HarperCollinsPublishers, 2015)
Escaping her ritzy Florida life and her cheating husband, Portia Kane returns to the South Jersey home of her youth and resolves to save herself by assisting a beloved English teacher who has retired after a traumatic incident.
Keywords: Families -- Fiction; Humorous fiction